Dynamics of productivity and cost of labor in Italian Manufacturing firms - Giulio Bottazzi; Marco Grazzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper studies the impact of size on labor cost and productivity for Italian manufacturing firms. The distributions of both labor cost and productivity display a wide support, even when disaggregated by sector of industrial activity. Further, both labor cost and productivity, when considered alone, are growing with the size of the firm. We investigate this relationship on a new set of data and we are able to show that once accounted for productivity differences among firms, size still retains a positive effect on cost of labor in most of the sectors considered.
Keywords: D21; J31; L11; L60; 330